Sternocleidomastoid pyomyositis mimicking parotid abscess - Soleh, Mohd Najeb; Mohamad, Irfan (Bangladesh Journal of Medical Science, 2010)
Pyomyositis is a condition of acute bacterial infection of skeletal muscle. It is commonly seen in tropical region, and the presentation depends on the site of involvement. We report a 72 year old lady presenting with swelling of left angle of mandible which mimicking left parotid abscess. Later on, imaging and operative findings proved it to be an intramuscular sternocleidomastoid abscess. Keywords: Pyomyositis; mimic; parotid abscess. DOI: 10.3329/bjms.v9i4.6692 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.238-240